The impact of comorbidities on surgical outcome and mortality in minimally invasive mitral valve surgery: a systematic review - Zwaans, Vanessa I. T.; Stein, Julia; Goecke, Simon; Pitts, Leonard; Akansel, Serdar; Kofler, Markus; Jacobs, Stephan; Falk, Volkmar; Kempfert, Jörg; Wert, Leonhard (Frontiers in Cardiovascular Medicine, 2025)
BackgroundWe sought to outline perioperative patient data to analyse surgical, clinical and echocardiographic outcomes and mortality of patients undergoing minimally invasive mitral valve surgery.MethodsSystematic literature research was performed in MEDLINE/PubMed according to PRISMA guidelines. Our research considered original works published until January 31, 2025. A pooled meta-analysis of studies reports early and late follow-up data of mitral valve repair for complex mitral valve regurgitation. In order to outline possible adverse events and comorbidities, we compared patients' mortality by differentiating preoperative, intraoperative and postoperative data.ResultsThis review analysed publications involving 222,947 patients, of which 43.4% were female and 56.6% were male, who underwent minimally invasive mitral valve surgery (MIMVS). The patients had a median age of 63.40 years (IQR: 60.42, 68.00), an average BMI of 25.1 kg/m2 (±7.9) and BSA of 1.7 m2 (±0.2). Severe mitral insufficiency was present in 86.4% of patients, 10% showed mild to moderate mitral insufficiency and 3.8% had mitral stenosis. The average EuroSCORE II showed a median value of 1.75% (IQR: 1.20, 2.95) and NYHA class III was most frequent. Comorbidities such as pulmonary hypertension were present in 35.37% of patients, diabetes mellitus in 8.57% (IQR: 4.76, 19.41), arterial hypertension was seen in 57.58% (IQR: 40.66, 68.79) with a significantly increased risk of mortality (p = 0.018). Coronary artery disease exhibited a prevalence of 17.41% (IQR: 10.78, 34.04), hypercholesterolaemia of 29.13% (IQR: 23.12, 49.74) and chronic kidney disease of 8.93% (IQR: 1.90, 20.00). New-onset atrial fibrillation occurred in 19.2% of patients. Besides this, 4% of patients required postoperative pacemaker implantation. Left atrial (LA) diameter decreased significantly from 50.37 mm preoperatively to 40.41%mm postoperatively (p < 0.001), LVDD was significantly reduced after MIMVS (p < 0.001). Mitral valve repair (75.83%) was considerably more common than replacement (21.09%). Applied techniques included annuloplasty (67.87%) and neochordal reconstruction (42.71%). Average mechanical ventilation was 540.8 min (±439.8), with a significant positive correlation between 30-day mortality and ventilation duration. In-hospital death occurred in 8 patients (±25), the average length of stay was 8.6 days (±3.9) and the mean postoperative ICU stay was 35.1 h (±15.9). Revision surgery was necessary in 4.1% of patients due to postprocedural bleeding. Postoperatively, 92% of patients showed no signs of MR, whereas 8% exhibited residual MR. Of those with residual MR, 78% continued to have mild MR, 14.9% had moderate MR and 7.1% showed severe mitral regurgitation after MIMVS.ConclusionsPostoperative mortality was associated with comorbidities like chronic kidney disease, diabetes mellitus and hypercholesterolaemia. Patients with a history of smoking, arterial hypertension or coronary artery disease showed variable risks, indicating that these factors may be associated with elevated in-hospital death or death within the first postoperative month. MIMVS shows favourable outcomes concerning echocardiographic measurements and haemodynamics such as LVEF, as well as length of hospital stay, ICU stay, postprocedural bleeding and complications such as wound infection or the need for blood transfusions.